Peran Orang Tua dalam Perkembangan Kognitif Anak di Sekolah Dasar di SD Negeri 1 Sumbang - Avisha, Sabrina; Bintaro, Tri Yuliansyah (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The development that occurs in children cannot be separated from the involvement of parents in raising and educating their children. The family is the first environment a child knows and plays a very important role in the child's growth and development. Therefore, the aim of this research is to determine the development of children's cognitive abilities in elementary school and the role of parents in children's cognitive development. This research uses a qualitative method with a case study approach, to find out in depth about the role of parents in children's cognitive development so that they can reveal and understand the true situation naturally. Data was obtained through interviews with students' parents and student observations. Data collection techniques include interviews, observation and documentation. The results of the research show that children have good cognitive abilities, although each child is different and parents play an important role in their children's cognitive development, because assistance from parents can provide a positive response to children, can influence children's growth and development.